The Influence of Brand Image, Price, and Product Quality on Consumers' Interest to Buy on Smartfren Quota Card in Rantauprapat - Hutabarat Tania Br; Nasution Zulkarnain; Hanum Fauziah (Quantitative Economics and Management Studies, 2023)
This study aims to analyze the effect of brand image, price and product quality on consumer buying interest on Smartfren quota cards in Rantauprapat. The research method used in this research is quantitative. In this study, the population is Smartfren Rantauprapat Quota Card consumers how much is unknown. The research sample using the incidental sampling technique is a sampling technique based on chance, that is, anyone who happens to meet the researcher can be used as a sample, if it is deemed that the person met by chance is suitable as a data source. This study uses a non-probability sampling technique because the population size is unknown, and purposive sampling is used as a sampling technique. Because the number of members of the population is not known with certainty, the sample size is calculated by the Cochran formula with a sample of 96 people. Data collection techniques used were observation, documentation studies and questionnaires. The method of analysis of this research is multiple linear regression with the SPSS program. The results of the study prove that brand image has a positive and significant effect on consumer buying interest on the Smartfren Quota Card in Rantauprapat. Price has a negative and significant effect on Consumer Purchase Interest on Smartfren Quota Cards in Rantauprapat. Product quality has a negative and significant effect on consumer buying interest on Smartfren Quota Cards in Rantauprapat. Brand Image, Price and Product Quality simultaneously have a positive and significant effect on Consumer Purchase Interest on Smartfren Quota Cards in Rantauprapat. The coefficient of determination of 0.375 means that Consumer Purchase Interest can be explained by the variables Brand Image (X1), Price (X2) and Product Quality (X3) of 37.5 %, while the remaining 62.5% can be explained by other variables not examined in this study. this research.